IMPROVING URBAN MANAGEMENT THROUGH E-GOVERNMENT SERVICES: THE ROMANIAN EXPERIENCE - PLUMB, Ion; ZAMFIR, Andreea (Theoretical and Empirical Researches in Urban Management, 2009)
The paper outlines the role of e-Government services within the process of improving urban management and the conceptual framework for measuring the e-Government services development. Furthermore, the progress on e-Government services in Romania is analyzed with a view to compare it with the sophistication stage achieved within the European Union. The findings of this study reveal that e-Government services are key tools for improving urban management and a higher level of e-Government services development is needed in order to transform the interactions between public administration and citizens/businesses. The study was carried out by combining a wide variety of sources, such as reports, regulations, and the national experience in developing e-Government services. Our conclusion justifies the effort invested in developing e-Government services and also has relevance for policy making in a very sensitive sector like the urban management. The methodology and the results reported in this research may be helpful for the specialists within the system in order to better address the inherent problems encountered in developing the e-Government services.